Acute respiratory infections in early childhood and risk of asthma at age 7 years - Forsström, Ville (My University, 2019)
Young children experience frequent acute respiratory infections (ARIs). Of these, lower respiratory tract infections are associated with an increased risk of developing childhood asthma. The association between upper respiratory infections and subsequent childhood asthma is not yet equally well understood. In this study, 923 children were followed with symptom diaries for ARIs from birth until two years of age. During ARIs, nasal swabs for respiratory viruses were acquired. Primary outcome was a diagnosed asthma in electronic medical records or a prescription for an inhalation corticosteroid at 6.5 to 7.5 years of age. The association between ARIs and the risk of asthma was evaluated using binary logistic regression analysis. Electronic prescriptions and medical records were available for 910 (99%) children. A total of 8795 ARIs were recorded, with a mean number of 6.2 (95% confidence interval [CI] 6.0-6.4) per child per year. Asthma was documented at age 7 years in 75 (8%) children. Increased number of ARIs (≥9/year vs <5/year) during 0-2 years of age was associated with an increased risk of asthma at age 7 (adjusted odds ratio 7.20, 95% CI 2.49‒20.88), as were more severe and prolonged ARIs. Children who developed asthma had more days with ARI symptoms per year before 2 years of age than other children (mean 65 vs 50, p=0.01). We found an association between early childhood ARIs and later childhood asthma. This association may stem from common pathophysiologic mechanisms, or ARIs in early childhood may be a predisposing factor to the development of asthma.
Keywords: asthma, children, respiratory infections